Colistin Resistance among Human Clinical Isolates from a Tertiary Care Hospital in Nepal - Amatya, R.; Barakoti, A.; Rai, J. R.; Subedi, A. (Kathmandu University Medical Journal, 2021)
Background Colistin is increasingly being used for treatment of multidrug resistant (MDR) bacterial infections in human. The plasmid mediated mcr-1 gene was detected recently among the poultry in Nepal. Plasmid mediated colistin resistance among human isolates would severely compromise the treatment of MDR bacterial infections. Objective To find out the prevalence of colistin resistance among the gram-negative bacteria isolated from clinical specimen. Method A descriptive cross-sectional study was conducted in a tertiary care hospital in Kathmandu. Colistin resistance among all the gram negative bacilli (GNB), isolated in a year, from all clinical specimen subjected for aerobic bacterial isolation, was detected by disc diffusion and agar dilution methods. Those with a minimum inhibitory concentration (MIC) > 2 mcg/ml were subjected to polymerase chain reaction for detection of mcr-1 gene. Result A total of 1993 aerobic GNB were isolated from clinical samples received from February 2018 to January 2019. By the agar dilution screening method, 2.1% of the GNBs isolated had MIC of colistin > 2 mcg/ml. None of these possessed the mcr-1 gene. Conclusion Given the occurrence of increased MIC of colistin in the clinical isolates in our set up, nationwide active surveillance would generate data for Nepal. The study for the presence of other genes (chromosomal or plasmid mediated) responsible for the increased MIC of colistin would further guide the control measures.